ON THE ROLE OF BACTERIAL MICROFLORA IN ETIOLOGY OF CHRONIC ADENOIDITIS IN CHILDREN - D. A. Tulupov; E. P. Karpova ("Paediatrician" Publishers LLC, 2014)
A review of the results of clinical studies on the role of pathogenic bacterial microflora in etiology of chronic adenoiditis in children is shown in this article. According to the literature data the main cause of the development of chronic diseases of the nasopharynx in children is viral infection. The role of the bacterial microflora is secondary, but nevertheless significant. The main bacterial pathogens isolated from the nasopharynx of children with chronic adenoiditis are Staphylococcus aureus, Haemophilus influenzae and Streptococcus pneumonia. However there is significant dissociation in the prevalence of these bacterial agents according to the data of different scientists. Ability of the bacteria to produce biomembranes plays significant role in formation of persistence of the above-mentioned pathogens in the nasopharynx in chronic adenoiditis. Bacterial biomembranes as well as the revealing of the large amounts of bacteria within the tissues of adenoids determines discussions on possibilities of systemic and topical antibacterial treatment.